Hubungan Motivasi dan Dukungan Keluarga dengan Kepatuhan Minum Obat Klien TB Paru Dewasa di Wilayah Kerja Puskesmas Kecamatan Duren Sawit Jakarta Timur Tahun 2019 - Suci Hartatik; Evi Vestabilvy (STIKes Persada Husada Indonesia, 2019)
Tuberculosis (TB) is still a major global health problem. According to WHO in 2013, there were around 8.6 million people fell ill with pulmonary TB and 1.3 million died from pulmonary TB. WHO set 22 countries in the world as countries with high TB ​​disease problems (high burden countries), that countries cover 63% of the world's population, around 80% of the estimated number of new TB cases that occur worldwide each year. This study aimed to determine the relationship of motivation and family support with adherence to take medication for adult Lung TB patients in the Work Area of ​​the Duren Sawit District of East Jakarta. The study design was quantitative with a cross-sectional approach. The population in this study were productive age pulmonary TB patients (15 to 59 years) who had undergone treatment for ≥ 6 months in the working area of ​​the Duren Sawit District Health Center in East Jakarta. The results showed the most dominant variable was the family support variable with a p-value of 0,000, OR 15,930, 95% CI (5,285-48,017), which means that good family support had a 15,930 times chance of complying with medication in patients with pulmonary TB compared to not good family support, and the confounding variable was gender the sex with a p-value of 0.175, OR 1,838 CI 95% (0.762-4,431) which means that gender is not related to adherence to taking medication in pulmonary TB patients.